1995
DOI: 10.2337/diacare.18.8.1156
|View full text |Cite
|
Sign up to set email alerts
|

1,5-Anhydro-D-glucitol Evaluates Daily Glycemic Excursions in Well-Controlled NIDDM

Abstract: The findings suggest that the plasma 1,5-AG concentration can be a useful index of the daily excursion of blood glucose, especially in patients with well-controlled NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 11 publications
1
47
0
Order By: Relevance
“…clinical study conducted in Japan, it was shown that 1,5-AG could be a useful index of glucose excursions in patients with reasonably well-controlled diabetes (mean A1C 7.1%) (15). Preliminary data from another study in Japan showed that 1,5-AG was an independent predictor of postprandial hyperglycemia and was more sensitive and specific than A1C (22).…”
Section: Conclusion -In a Previousmentioning
confidence: 99%
See 1 more Smart Citation
“…clinical study conducted in Japan, it was shown that 1,5-AG could be a useful index of glucose excursions in patients with reasonably well-controlled diabetes (mean A1C 7.1%) (15). Preliminary data from another study in Japan showed that 1,5-AG was an independent predictor of postprandial hyperglycemia and was more sensitive and specific than A1C (22).…”
Section: Conclusion -In a Previousmentioning
confidence: 99%
“…Thus, 1,5-AG responds sensitively and rapidly to changes in serum glucose, reflecting even transient elevations of glucose within a few days (13,14). 1,5-AG has been shown to reflect daily glycemic excursions in patients with A1Cs at or near goal (15). In contrast, A1C is an index of average glucoses over a much longer period of time (2-3 months), encompassing both hyperglycemia and hypoglycemia.…”
mentioning
confidence: 99%
“…whose HbA1c levels are at or near the goal [7,8], and 1,5-AG levels have been reported to reflect postprandial glucose values in diabetic patients [9,10]. 1,5-AG levels are also considered a useful indicator of glycemic control, because they correlate with fasting plasma glucose and HbA1c levels [11,12], and they have been suggested to be a predictor of microvascular complications, such as diabetic retinopathy [13].…”
mentioning
confidence: 99%
“…1992, 1996), reflecting even transient elevations of glucose within the past few days and thereby serving as a measurement which is informative of glycemic excursions even in patients with normal HbA1cs (Kishimoto et al. 1995). Indeed, 1,5‐AG has been associated with risk of developing diabetes independently of HbA1c and fasting glucose concentrations (Juraschek et al.…”
Section: Introductionmentioning
confidence: 99%